Harvard Business Review Mckinsey Award Winners - Authors (Harvard Business Press, 2009)
For the past 50 years, the McKinsey Foundation for Management Research has offered awards for the best articles published each year in HBR. These awards, judged by an independent panel of leaders in the business community, recognize outstanding works that are likely to have a major influence on the actions of business managers worldwide.